A profile of the steel industry : global reinvention for a new economy - Warrian, Peter. (Industry profiles collection., 2016)
The steel mill and the auto plant were the icons of the 20th-century industrial economy. By the early 21st century, many people viewed steel as Big, Ugly, and Gone to China. Not so. In manufacturing, The World Is Not Flat! The steel industry has continuously been forced to remake itself. This book describes those developments and dynamics.